(untitled) (Coordinates of Public Administration, 2025)
The article conceptualizes the organizational arrangements for managing the development of urbanized territories in the Ivano-Frankivsk City Territorial Community as an integrated institutional and functional system encompassing a set of actors, mandates, procedural regulations, and resource frameworks. This system ensures coherence between strategic planning, spatial development, infrastructure investment, and the day-to-day delivery of municipal services. It is substantiated that, under conditions of growing uncertainty — wartime threats, fiscal constraints, migration dynamics, and climate-related risks — the decisive attribute becomes the controllability of urban development, understood as the capacity of executive bodies to establish a normative and priority-setting framework and to ensure coordination, while municipal enterprises implement managerial decisions through continuous service processes and recovery projects. Based on the synthesis of scholarly evidence, a functional model of urban governance is developed and adapted to the local context, comprising strategic, regulatory, investment-and-project, service-delivery, oversight, and communication components. To support applied design of organizational change, the article proposes a matrix allocating governance functions across implementing entities («governance functions → implementers»). Priority directions for strengthening the community’s organizational capacity are identified, including: harmonization of mandates and responsibility areas of профильні (line) departments; introduction of performance contracting mechanisms for municipal enterprises; development of municipal analytics and open data systems as governance tools; and standardization of interagency protocols for planning and delivering urban recovery projects.